HUBUNGAN RESPON TIME PERAWAT DENGAN KEPUASAN KELUARGA PASIEN DI INSTALASI GAWAT DARURAT (IGD) RS. BHAYANGKARA TKT. III MANADO - Donny Sahensolar; Michelle Kairupan (Yayasan Syalom Cipta Sumikolah, 2024)
Service response time can be calculated in minutes and is greatly influenced by various things, both regarding the number of personnel and other supporting components (Andriani, 2023). The need for appropriate and efficient response time plays an important role in every decision made from the moment the patient arrives until the patient is transferred from the Emergency Room. Satisfaction is said to be an increased feeling after a comparison of skills or that the perceived results feel better than expected. The aim of this research is to determine the relationship between nurse response time and patient family satisfaction in the Emergency Room (IGD) Bhayangkara Tkt III Manado Hospital. The type of research used in this research is quantitative with a descriptive analytical approach, statistical tests in the research use the chi square test (x2) or cross sectional study. The population in this study was the families of patients in the Bhayangkara Hospital emergency triage in the last 3 months from January to March 2024 totaling 256 people, the monthly average was 85 people. The sample in this study used a sampling method, namely total sampling. So the sample in this study was 85 people. Data were analyzed using the Chi-Square statistical test with a significance level of 95% (α): 0.05. Based on the results of statistical tests using the Chi-Square Test, it was obtained that ρ-value = 0.000 was smaller than the value α = 0.05. This means that H0 is rejected, so there is a relationship between nurse response time and patient family satisfaction in the Emergency Room (IGD) of Bhayangkara Tkt III Manado Hospital.